BIOMETHANE PRODUCTION BY LICENSED BRAZILIANS LANDFILLS AND POTENTIAL ENERGY USE IN SMALL MUNICIPALITIES - Ritter, Elisabeth; Guerreiro, Erica; Ornelas-Ferreira, Bernardo (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2022)
One of the main challenges especially for small developing cities is finding economically viable alternatives to the management of municipal solid waste. This research aims to investigate the potential of biomethane production by licensed Brazilian landfills, in order to assess the feasibility of using biomethane energy in small municipalities. This study identified three biogas-upgrading facilities authorized by the Brazilian National Agency of Petroleum, Natural Gas and Biofuels (ANP) as to know: GNR Dois Arcos, Gás Verde and GNR Fortaleza. Field research collected additional information about the landfills and biomethane facilities investigated, in order to create indexes for supporting decision-makers in the waste management sector. Indexes A and B were proposed, which represent: the relation between the biogas production and the mass of landfilled municipal solid waste, and the relation between the biomethane processing capacity in the facility and the biogas production potential, respectively. This study showed that one of the facilities with lower biomethane production and biogas processing capacities, and which receives municipal solid waste from several small municipalities - such as GNR Dois Arcos - presented a similar value for index A in relation to the biggest facility – such as Gás Verde - and the highest value for index B compared to the other two larger facilities.